Levels of Heavy Metals in Selected Canned Fish on Cape Coast Market, Central Region, Ghana - Benjamin, Bartels; Kenneth, Apaah Brakye; Yao, Gadzekpo Victor Patrick (International Journal of Environment, Agriculture and Biotechnology, 2023)
Background and objectives: The sea is polluted with heavy metals that accumulate in fishes. Consumption of these fishes pose health risk. The aim of this study is to respectiely assess the concentrations and health risks of lead (Pb), zinc (Zn), iron (Fe), tin (Sn), manganese (Mn), and mercury (Hg) in canned fish samples. Methods: The study focused on Mackerel, Sardine and Tuna. Mackerel brands are African Queen, Geisha, Ena Pa, and Milano; Sardine includes Titus, Festiva, Ohemaa, and Princess, while Tuna were Lele and Star Kist. Flame Atomic Absorption Spectrophotometry was used. Results: The mean concentrations of lead and mercury in the Mackerel, Sardine and Tuna were respectively 0.142± 0.017, 0.122±0.034, 0.141±0.006 µg/g and 0.126± 0.017, 0.132± 0.012, 0.263± 0.006 µg/g below the recommended limits of 0.3 and 0.5 µg/g by EU Reg. No 1881/2006. The concentrations of zinc, iron, tin, and manganese were within the acceptable respective limits. A health risk assessment based on the criteria established by the US EPA revealed no significant health risks associated with the concentrations of the metals. Conclusion: The canned fish samples exhibited low levels of heavy metal contamination, indicating that the fish samples pose no significant health risks to consumers